Overview of Informal Sector Workers Viewed from Education Variables - Dodi Satriawan (The Journal of Indonesia Sustainable Development Planning, 2023)
The Special Region of Yogyakarta has a significant population engaged in the informal sector. This study aims to explore the relationship between educational level and participation in the informal sector. The data used in this study is from the August 2022 Sakernas (National Labor Force Survey) data. Descriptive analysis was employed to address the research objectives. The research findings reveal that over half of the population is employed in the informal sector. Workers with higher levels of education tend to transition to the formal sector, while less educated individuals dominate the informal sector. Education not only influences sectoral choices but also has an impact on conditions within the informal sector. Workers with higher education experience better conditions, regardless of the field of business, working hours, or income level. They engage in businesses that require capital, demonstrating organization, efficiency, and higher earnings. Some educated informal workers take part-time jobs while waiting for other opportunities.